ANALYSIS OF CREDIT POLICY AND PROCEDURE AT PT. BANK SULUT - Sarajar, Pinky (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Bank is a financial institution which has a role as mediator between money depositors and parties who have a need of the money. Depositors invest their money in the bank in form of bank deposits, savings, and other products of the bank. Whereas those who need it acquire the fund in form of bank loans or credit. Those who acquire the funds called debtors. Research objective is to analyze credit policy and procedure at Bank Sulut. Theories supporting this research are financial management, bank, and credit. The sample of this research is the documents of credit policy and procedure. Population of this research are the credit analysts in PT. Bank Sulut with 8 key respondents. Results and conclusions are even though there are credit policies and procedures in PT. Bank Sulut, bad debts still happen. It is because of lack of knowledge or even caring by debtors or even the internal of PT. Bank Sulut. The examination of credit application and monitoring must be held properly by well-trained analysts. Keywords: financial management, credit policy